New species and occurrences of Caperonia (Euphorbiaceae) for South America - Külkamp, Josimar; Iganci, João R. V.; Cordeiro, Inês; Baumgratz, José Fernando A. (Phytotaxa, 2021)
Caperonia (Ditaxinae, Euphorbiaceae) has ca. 34 species distributed in the Americas and Africa, with approximately 26 of them occurring in South America. The species are exclusively of open marshy environments. The new species Caperonia amarumayu and C. maracaibensis, from Bolivia and Venezuela respectively, are hereby described. We also designate a lectotype, and report two new occurrences of C. zaponzeta for Bolivia and Brazil.